THE EFFECT OF THE LIGHT SELECTIVE COVER AND SPRAYING WITH PACLOBUTRAZOL ON THE VEGETATIVE GROWTH OF ANTIRRHINUM MAJUS PLANTS - & et al., Al-Mahdawe (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This study was conducted on Antirrhinum majus plant to investigate the effect of the light selective and colored covers red, yellow and control with spraying by paclobutrazol in three concentrations (0,50 and100 mg.L-1) on some vegetative growth. The factorial experiment was carried out within Randomized Complete Block design using three replicates with six plants for each replicate. Results indicated that there was a significant decrease in the plant characters grown under the red and yellow polyethylene covers in comparison with the plants grown under the control cover. These characters were the plants height, number of the internodes, number of branches, diameter of the crown area, number of leaves, leaf area and the total carbohydrate in the leaves the mean values were: 14.84, 17.31 cm, 7.66, 7.11 internode per plant-1, 8.55, 7.77 branch per plant-1, 15.33, 15.44cm, 112.66, 108.55 leaf per plant-1, 1861.6, 1458.7 cm², 43.74, 51,11 % respectively. Also, there was a significant increase in the ratio of chlorophyll in the leaves which was 40.33 and 39.11Spad unit, respectively. Spraying with paclobutrazol at 50 and 100 mlg.L-1 led to a significant decrease in the plant height 18.46 and 18.80cm and number of leaves 110.33 and 111.55 leaf per plant-1 respectively, whereas there was no significant effect on the other characters of the plants sprayed with both concentrations of paclobutrazol.